Philological Quarterly: tomo 27 (1948), tomo 28 (1949), tomo 29 (1950), tomo 30 (1951), tomo 31 (1952). - Alatorre, Antonio (El Colegio de México, 1958)
Se reseñó: Philological Quarterly: tomo 27 (1948), tomo 28 (1949), tomo 29 (1950), tomo 30 (1951), tomo 31 (1952).